Ghrelin treatment reverses the reduction in weight gain and body fat in gastrectomised mice. Issue 7 (21st April 2005) - Dornonville de la Cour, C; Lindqvist, A; Egecioglu, E; Tung, Y C L; Surve, V; Ohlsson, C; Jansson, J-O; Erlanson-Albertsson, C; Dickson, S L; Håkanson, R
Abstract : Background and aims: The gastric hormone ghrelin has been reported to stimulate food intake, increase weight gain, and cause obesity but its precise physiological role remains unclear. We investigated the long term effects of gastrectomy evoked ghrelin deficiency and of daily ghrelin injections on daily food intake, body weight, fat mass, lean body mass, and bone mass in mice. Methods: Ghrelin was given by subcutaneous injections (12 nmol/mouse once daily) for eight weeks to young female mice subjected to gastrectomy or sham operation one week previously. Results: Gastrectomy reduced plasma concentrations of total ghrelin (octanoylated and des-octanoylated) and active (octanoylated) ghrelin by ∼80%. Immediately after injection of ghrelin, the plasma concentration was supraphysiological and was still elevated 16 hours later. Daily food intake was not affected by either gastrectomy or ghrelin treatment. The effect of ghrelin on meal initiation was not studied. At the end point of the study, mean body weight was 15% lower in gastrectomised mice than in sham operated mice (p<0.001); daily ghrelin injections for eight weeks partially prevented this weight loss. In sham operated mice, ghrelin had no effect on body weight. The weight of fat was reduced in gastrectomised mice (−30%; p<0.01). This effect was reversed by ghrelin, enhancing the weight of fat in sham operated mice also (+20%; p<0.05). Gastrectomy reduced lean body mass (−10%; p<0.01) and bone mass (−20%; p<0.001) compared with sham operated mice. Ghrelin replacement prevented the gastrectomy induced decrease in lean body mass but did not affect bone. In sham operated mice, ghrelin affected neither of these two parameters. Conclusions: Ghrelin replacement partially reversed the gastrectomy induced reduction in body weight, lean body mass, and body fat but not in bone mass. In sham operated mice, ghrelin only increased fat mass. Our results suggest that ghrelin is mainly concerned with the control of fat metabolism and that ghrelin replacement therapy may alleviate the weight loss associated with gastrectomy.